The Efficacy of a Scaffold-free Bio 3D Conduit Developed from Autologous Dermal Fibroblasts on Peripheral Nerve Regeneration in a Canine Ulnar Nerve Injury Model: A Preclinical Proof-of-Concept Study. Issue 9 (September 2019) - Mitsuzawa, Sadaki; Ikeguchi, Ryosuke; Aoyama, Tomoki; Takeuchi, Hisataka; Yurie, Hirofumi; Oda, Hiroki; Ohta, Souichi; Ushimaru, Mika; Ito, Tatsuya; Tanaka, Mai; Kunitomi, Yoshihiro; Tsuji, Manami; et al.
Autologous nerve grafting is widely accepted as the gold standard treatment for segmental nerve defects. To overcome the inevitable disadvantages of the original method, alternative methods such as the tubulization technique have been developed. Several studies have investigated the characteristics of an ideal nerve conduit in terms of supportive cells, scaffolds, growth factors, and vascularity. Previously, we confirmed that biological scaffold-free conduits fabricated from human dermal fibroblasts promote nerve regeneration in a rat sciatic nerve injury model. The purpose of this study is to evaluate the feasibility of biological scaffold-free conduits composed of autologous dermal fibroblasts using a large-animal model. Six male beagle dogs were used in this study. Eight weeks before surgery, dermal fibroblasts were harvested from their groin skin and grown in culture. Bio 3D conduits were assembled from proliferating dermal fibroblasts using a Bio 3D printer. The ulnar nerve in each dog's forelimb was exposed under general anesthesia and sharply cut to create a 5 mm interstump gap, which was bridged by the prepared 8 mm Bio 3D conduit. Ten weeks after surgery, nerve regeneration was investigated. Electrophysiological studies detected compound muscle action potentials (CMAPs) of the hypothenar muscles and motor nerve conduction velocity (MNCV) in all animals. Macroscopic observation showed regenerated ulnar nerves. Low-level hypothenar muscle atrophy was confirmed. Immunohistochemical, histological, and morphometric studies confirmed the existence of many myelinated axons through the Bio 3D conduit. No severe adverse event was reported. Hypothenar muscles were re-innervated by regenerated nerve fibers through the Bio 3D conduit. The scaffold-free Bio 3D conduit fabricated from autologous dermal fibroblasts is effective for nerve regeneration in a canine ulnar nerve injury model. This technology was feasible as a treatment for peripheral nerve injury and segmental nerve defects in a preclinical setting.